Development of a Biology E-Module Based on Google Sites on Circulatory System and Digestive System Material - Yogi Valfa; Abdul Razak; Suci Fajrina; Elsa Yuniarti (Jurnal Penelitian Pendidikan IPA, 2023)
Technological developments have a big influence on the learning process. Various positive influences can be seen with technological developments, one of which is electronic learning media. The existence of electronic-based media has a positive impact on learning because of the various advantages it has. In reality in the field, there are still many biology teachers who do not use electronic learning media in the learning process. Learning media that does not utilize technology tends not to attract students' attention due to its monotonous nature. Based on these reasons, researchers developed electronic learning media in the form of e-modules based on Google sites. E-module is able to visualize and clarify various abstract concepts. E-modules can help teachers to facilitate students in learning and support the learning process. The development of a Google Sites-based e-module was created using the Plomp model which consists of 3 stages, namely the initial investigation stage (preliminary research), the development or prototyping phase (development or prototyping phase), and the assessment phase (assessment phase). The results of the e-module development show that the overall validation value of the Google Sites-based e-module is 86.40% (very valid) from experts. Furthermore, the practicality assessment given by the teacher towards the Google Sites-based e-module showed an average result of 96.25% (very practical).